Semi-Discrete and Fully Discrete Hybrid Stress Finite Element Methods for Elastodynamic Problems. Issue 4 (10th November 2015) - Yu, Zhengqin; Xie, Xiaoping
Abstract: This paper proposes and analyzes semi-discrete and fully discrete hybrid stress finite element methods for elastodynamic problems. A hybrid stress quadrilateral finite element approximation is used in the space directions. A second-order center difference is adopted in the time direction for the fully discrete scheme. Error estimates of the two schemes, as well as a stability result for the fully discrete scheme, are derived. Numerical experiments are done to verify the theoretical results.